PERKEMBANGAN DAN PERUBAHAN KURIKULUM PENDIDIKAN ISLAM DI INDONESIA (Tinjauan Historis, Sosiologis, Politis, Ekonomi dan Manajemen Negara) - Husin Husin (Program Studi PAI STAI Al Falah Banjarbaru, 2018)
The curriculum in its journey always developing and changes according to the development of science. Not only that, political, economic, social and cultural factors also become a matter of concern in curriculum change. Islamic educational institutions such as Madrasah in the implementation of education must always evolve in accordance with the conditions of curriculum development that exists. But as an educational institution whose main purpose is to shape the character of learners who are not only able to answer the needs of society, Islamic education institutions must also be able to answer the needs of the market. Moreover, Indonesia has entered the AEC (ASEAN Economic Community) which allows the free market among ASEAN countries so that Islamic education institutions must also grow up so as not to be left behind with other countries. Keywords: Curriculum, Job Vacancy, Social Needs.